Field Study of Vegetated Channel at UTHM Campus - Ahmad, Noor Aliza; Kasmin, Hartini; Daud, Nabila (International Journal of Integrated Engineering, 2024)
A vegetated channel refers to a form of infrastructure that aims to mitigate stormwater runoff through the utilization of either natural or constructed systems that replicate the behavior observed in natural environments. The condition of the vegetated channel has the potential to influence the hydraulic behavior of the channel. The regulation of stormwater quantity in the management of drainage systems is influenced by the characteristics of the vegetated channel. Field data was gathered from a channel located in the parking lot of the Faculty of Civil Engineering and Built Environment at the University Tun Hussien Onn Malaysia (UTHM) campus. The purpose of this data collection was to assess the influence of various sectional circumstances on the velocity profile. The measurement of stream flow velocity is conducted by the utilization of current meter equipment during field investigation. The Manning's coefficient for each section was analyzed to assess the impact of variations in this parameter on the flow rate of the channel. In accordance with the results obtained, the coefficient value of Manning's ranged from 0.160 to 0.826. The velocity of flow in the vegetated channel ranged from 0.003 m/s to 0.010 m/s. In the interim, the flow discharge magnitude for the channel exhibits variability within the range of 0.0005 m3/s to 0.002 m3/s. This study examines the impact of bed surface condition, channel slope, and Manning's coefficient on flow rate. Therefore, the flow rate and Manning's coefficient were found to be impacted by both the bed condition and the slope of the channel.